Principles and practice in biobank governance - Kaye, J; Stranger, M (Ashgate Publishing Ltd, 2009)
Rapid technological advances, the establishment of large-scale biobanks, and the exchange of data across international boundaries raise a variety of questions for regulators struggling with the problem of how to govern such stores of information and the processes connected with them. Engaging with the pressing issues of privacy, consent, access to data, and benefit sharing, Principles and Practice in Biobank Governance draws together the latest empirical research from the UK, Europe, America, Australia and Asia to focus on these challenges. Current models of governance are critiqued, principles and policies are debated, and new models and theoretical frameworks are presented through this intellectually stimulating, informative volume. This truly international volume offers new insights from a range of disciplinary perspectives and will be essential reading for policy makers and scholars across a range of social sciences, including sociology, bioethics, law and social policy. © Jane Kaye and Mark Stranger 2009. All rights reserved.